2020
DOI: 10.1002/jimd.12271
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning and depressive symptoms in Fabry disease: A follow‐up study

Abstract: Patients with Fabry disease (FD) have a high prevalence of depressive symptoms and can suffer from cognitive impairment, negatively affecting their life. The course of cognitive functioning and depressive symptoms in FD is unknown. The aim of this prospective cohort study was to describe changes in cognitive functioning and depressive symptoms and to identify related variables in patients with FD over 1 year. Assessments were conducted twice, using a neuropsychological test battery and the Centre of Epidemiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…However, normal cognitive performance was reported in memory, naming, perceptual functioning, and global cognitive functioning ( 16 – 18 ). Recently, prospective longitudinal studies reported normal cognition at baseline and two follow-ups [2-8 years after the baseline ( 31 )], suggesting a stable disease course. Körver et al ( 32 ) reported no major changes in cognition of 76 FD patients on one-year follow-up.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, normal cognitive performance was reported in memory, naming, perceptual functioning, and global cognitive functioning ( 16 – 18 ). Recently, prospective longitudinal studies reported normal cognition at baseline and two follow-ups [2-8 years after the baseline ( 31 )], suggesting a stable disease course. Körver et al ( 32 ) reported no major changes in cognition of 76 FD patients on one-year follow-up.…”
Section: Resultsmentioning
confidence: 99%
“…One of the most important is male sex (OR, 6.8; 95%CI, 1.6-39.8; p = 1.6 *10-2) ( 32 ). Körver et al showed that male sex is associated independently with cognitive impairment at baseline, but there were no changes related to sex in neuropsychological assessment after one-year follow-up ( 31 ). The study of Sigmundsdottir et al ( 33 ) reported that males with FD had a slower speed of information processing, reduced performance in executive functions (verbal generation, reasoning, problem-solving, perseveration), and they were more likely to show clinically significant limitations.…”
Section: Resultsmentioning
confidence: 99%
“…We saw significant correlations between HADS depression score and both BPI interference and fatigue in our cohort. Whatever the etiology may be, given the magnitude and implications of psychiatric symptoms in FD, an increased focus on diagnosis and treatment of depression is warranted 19,76 …”
Section: Discussionmentioning
confidence: 99%
“…Concerning psychological interventions, a recent study assessing changes in depressive symptoms after a 1-year follow-up found no difference when comparing CES-D scores between patients that received a counselling intervention and those who did not [52]. On the contrary, a small study assessing the effects of a counselling intervention administered by a psychotherapist and utilizing cognitive-behavioural strategies and insight-oriented techniques tailored to each patient particular situation improved depression in FD patients for up to 6 months after concluding the intervention.…”
Section: Treatment Of Depression In Patients With Fabry Diseasementioning
confidence: 99%